Analisis Keselamatan dan Kesehatan Kerja (K3) menggunakan Metode Hirarc pada PT PLN (Persero) ULP Ujungberung - Happy Zahwa Azzahra; Resi Juariah Susanto (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
This study aims to analyze the implementation of Occupational Health and Safety (OHS), identify workplace hazards, assess occupational risk levels, and formulate appropriate risk control recommendations for field technicians at PT PLN (Persero) ULP Ujungberung. The research was motivated by the suboptimal implementation of OHS, as indicated by an OHS achievement score of 83.8 out of 100 and an increasing number of work-related incidents that have the potential to affect employee safety and operational performance. A mixed-method approach was employed by combining qualitative and quantitative data collected through interviews, direct observations, and documentation. Hazard identification and risk assessment were conducted using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method based on the AS/NZS 4360:2004 standard. The findings identified 15 major work activities involving mechanical, physical, environmental, and electrical hazards. Six activities (40%) were categorized as extreme risk and another six activities (40%) as high risk, with electric shock and falls from height identified as the most critical hazards. Recommended control measures include strengthening the grounding system, consistently implementing safety briefings and Job Safety Analysis (JSA), improving compliance with personal protective equipment (PPE), and applying reward and punishment programs to strengthen the company's commitment toward achieving the Zero Accident target.